2021
DOI: 10.1111/and.14038
|View full text |Cite
|
Sign up to set email alerts
|

The association between plant‐based diet and erectile function in Chinese young healthy men: A population‐based study

Abstract: The study was designed and conducted to evaluate the plant‐based diet status and its association with erectile function (EF) in Chinese young healthy men. From July 2018 to May 2020, 116 objectively proved physically and psychologically healthy men were selected. Clinical questionnaires, detailed physical examinations and blood tests were all assessed. An overall plant‐based diet index (PDI) and a healthful plant‐based diet index (hPDI) were developed from each participant to measure plant‐based diet quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Several prospective cohort, cross‐sectional, and case–control human studies have been conducted to assess the association between dietary habits and EF, mainly assessed through the International Index of Erectile Function‐5 (IIEF‐5) questionnaire or a five‐point Likert scale (Table 1). Overall, a higher intake of fruits and/or vegetables was associated with lower odds of having or developing ED in most, 34–38 but not all studies 39,40 . Interestingly, a study conducted by Chen et al 41 .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Several prospective cohort, cross‐sectional, and case–control human studies have been conducted to assess the association between dietary habits and EF, mainly assessed through the International Index of Erectile Function‐5 (IIEF‐5) questionnaire or a five‐point Likert scale (Table 1). Overall, a higher intake of fruits and/or vegetables was associated with lower odds of having or developing ED in most, 34–38 but not all studies 39,40 . Interestingly, a study conducted by Chen et al 41 .…”
Section: Resultsmentioning
confidence: 93%
“…Overall, a higher intake of fruits and/or vegetables was associated with lower odds of having or developing ED in most, 34 , 35 , 36 , 37 , 38 but not all studies. 39 , 40 Interestingly, a study conducted by Chen et al. 41 reported that a higher intake of vegetables was also associated to worse ED.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results could provide more evidence for the clinical utilization of TRT for treating LOH and guiding the dietary recommendations for LOH patients. Lu's report also reported that the intake of plant-based diet could be beneficial to erectile function in men over 45 yeas old and without impacting total testosterone level (66,67). Therefore, incorporating a diet that fosters testosterone production and includes plant-based elements could be beneficial for LOH patients.…”
Section: Discussionmentioning
confidence: 98%
“…The number of consumers of vegan and vegetarian diets has been observed to increase, and the Mediterranean Diet (MD) is considered a healthy choice as well. Between 2014 and 2017, there was a 5-fold increase in the number of plant-diet followers [ 50 ]. Various studies show differences between vegan and non-vegan diet patterns.…”
Section: Diet Factors Vs Metabolic Syndromementioning
confidence: 99%